Pemodelan 3D Eksterior Masjid Al-Syuro Menggunakan Teknologi TLS dan Fotogrametri Drone - Rasyid, Muhammad Haikal; Kartini, Gusti Ayu Jessy (Jurnal Serambi Engineering, 2025)
Al-Syuro Mosque in Garut, designated as a National Cultural Heritage Site, features distinctive Art Deco architecture and requires detailed spatial documentation for preservation amid urban development threats. This study aims to produce a 3D exterior model of the mosque by integrating Terrestrial Laser Scanner (TLS) and Unmanned Aerial Vehicle (UAV) photogrammetry technologies. TLS data were acquired using a Leica RTC360, generating 18 scans registered with the cloud-to-cloud method (RMSE 0.003 m). UAV data were captured using a DJI Phantom 4 Pro V2 at a 40-meter altitude, resulting in 115 images and 3 Ground Control Points (GCPs). The images were processed with Agisoft Metashape for photo alignment and georeferencing. The two point clouds (totaling 655 million points) were integrated in Cyclone 3DR using N-point registration, followed by filtering to yield 274 million points. The 3D model was then generated using Scan-to-Mesh meshing and texturing techniques. Validation using 16 sample objects showed no significant difference between the 3D model and actual field measurements (t-test, 95% confidence interval). Despite limitations in certain areas due to obstructions and drone specs, the combined TLS–UAV approach proves effective for comprehensive 3D documentation to support conservation, restoration, and heritage management efforts.